Bevölkerungsalterung unter Pandemiebedingungen - Jonas Schöley (Wirtschaftsdienst, 2023)
– In December 2022, the German Pension Insurance announced an estimated surplus of exteuro2.1 billion for the past year. President Roßbach partly explained this balance was due to the 'Corona Pandemic, which has led to an increase in mortality, especially among older people'. Here, the author takes a closer look at the demographics behind that statement and calculates the pandemic-related population deficit among ages 65 and above across Europe. The article also looks at population aging under conditions of continuously reduced life expectancy.
Keywords: H23; O25; R48; 330; Alternde Bevölkerung; Sterblichkeit; Epidemie; Deutschland; Europa